Ethical Discretion in Medical Record Disclosure: Legal Protection for Doctors in Acute Appendicitis Cases - James Davidta Ginting; Oksidelfa Yanto; Agus Purwanto (Sinergi International Journal of Law, 2026)
Medical confidentiality is a fundamental duty for physicians, and disclosing patient records is generally prohibited by law and professional ethics. However, life-threatening emergencies raise the question of whether such disclosure can be legally justified to protect a patient’s life. This study examines how Indonesian law addresses this dilemma and whether physicians have a defensible legal basis for disclosure in emergency situations. Using a normative juridical approach that reviews legislation, scholarly writings, and ethical guidelines, the research finds that Indonesian statutory law does not yet clearly regulate discretionary disclosure by physicians in conscious emergency refusal situations. As a result, physicians who disclose records to manage emergencies face uncertain legal protection. Nonetheless, interpretive principles such as lex specialis and the maxim salus populi suprema lex esto may justify limited disclosure when the goal is life preservation. Within this framework, disclosure may be considered lawful if proportional, narrowly confined to the emergency, and properly documented. The study concludes that clearer statutory provisions are needed to establish exceptions to confidentiality in emergencies. Such reforms would enhance legal certainty and strengthen protection for medical personnel who act in good faith, balancing ethical obligations with humanitarian imperatives.